A geographic information system application to visualize and manage data - Wurtz, Joshua (Kansas State University, 2015)
A geographic information system (GIS) allows an individual to map, model, query, and analyze large quantities of data from a database according to their spatial locations. This project uses the ArcGis Java software Development Kit (SDK) to visualize, manipulate, and comprehend large amounts of publicly available information relevant to a spatial location. The application developed uses a graphical user interface to examine the public data of Riley County, Kansas. The user is able to load shapefiles through the interface and then examine the many spatial locations. By examining a spatial location the user is able to view the associated attribute information, manipulate it, and add additional attributes. Beyond viewing information at selected geometric locations, a user can also query the layer(s) to return the spatial locations that fit the query. These abilities can allow a user to understand and visualize patterns that they would not have been able to easily see from looking at the raw data. Increasing users' understanding of the environment they are working with improves their likelihood of success in their desired objectives.
Keywords: Geographic information applicationGeographic information system; Computer Science (0984); Geographic Information Science and Geodesy (0370)